Caking kinetics of freeze-dried papaya determined by optica microscopy - Calori, Israel; Giarola, Tales Marcio Oliveira; Cal-Vidal, José (Pesquisa Agropecuaria Brasileira, 1997)
The caking kinetics of freeze-dried papaya (Carica papaya L.) was estimated based on the environmental conditions of relative humidity (31, 52 and 89%) and of temperature (10 and 25 °C). The caking kinetics was established from photomicrographics obtained by an optical microscope used at different time intervals. The results showed the influence of temperature and relative humidity on the degree of caking and the possibility of utilizing a simple method for analysis of caking on freeze-dried fruit powders.
Keywords: fruit caking; microstructure of powders